Elements of Change in the 2013 Curriculum and Its Impact on the Development of The Islamic Education Curriculum at the YPI Islamic Madrasah Tsanaiyah in the Batang Kuis District - Fitri, Fitri; Arief, Ajie Al (LPPPIPublishing, 2025)
This study examines the elements of change in the 2013 Curriculum and its impact on the development of the Islamic Education curriculum at Madrasah Tsanawiyah YPI in Batang Kuis District. The 2013 Curriculum introduced a significant shift in the Indonesian education system by emphasizing a balanced development of knowledge, skills, and character rooted in spiritual and social values. This research employed a qualitative descriptive approach to provide an in-depth understanding of these changes. Data were collected through document analysis of official curriculum guidelines, books, scientific articles, and previous studies, as well as in-depth interviews with teachers and administrators at the madrasah. The findings show that changes in graduation standards, content, processes, and assessments have encouraged the implementation of contextual and value-based learning approaches, such as integrating religious practices, scientific learning methods, and comprehensive assessment strategies. However, several challenges remain, including limited teacher understanding of the curriculum framework, insufficient resources, heavy administrative workloads, and difficulties in assessing affective competencies objectively. These obstacles affect the effectiveness of curriculum implementation at the madrasah level. The study highlights the importance of ongoing professional development for teachers, improved infrastructure, and collaborative involvement of educators, parents, and policymakers to ensure that the goals of the 2013 Curriculum are fully realized. The findings provide valuable insights for enhancing Islamic Education curriculum development in response to current educational demands.